Hematene: A 2d Magnetic Material in Van Der Waals or Non-Van Der Waals Heterostructures) - Allende-Prieto, S (IOP Publishing Ltd, 2019)
In this article, we study theoretically the properties of hematene, a new antiferromagnetic 2D material exfoliated from hematite. Hematene is not a van-der Waals material, but it can still be obtained by liquid exfoliation of hematite crystals. Its properties might be quite different from those of the bulk and to establish such differences is one of the aims of this study. A detailed study of hematene by density functional theory has been carried out to look at the electronic properties of this iron oxide material. Results show that freestanding hematene is antiferromagnetic with a magnetic moment of 4 μB per atom and an insulator/semiconductor with a bandgap of almost 1.0 eV. The stability of hematene is confirmed by calculating its phonon spectrum. Hematene supported on gold and stanene was also investigated: while no significant changes are found for the contact with the former, the interaction with the latter turn Hematene into a 2D ferrimagnet. © 2019 IOP Publishing Ltd. All rights reserved.